Prognostic factors of brain metastases affecting survival: an Indonesian cohort - Koesbandono Koesbandono; Rusli Muljadi; Ratna Sutanto; Lutfi Hendriansyah; Erna Kristiani; Carissa Faustina; Jessica Christanti (Faculty of Medicine, Universitas Trisakti, 2025)
BackgroundBrain metastases (BMs) most frequently originate from primary tumors of the lung and breast, and significantly impact cancer patient prognosis. Metastases can be detected synchronously along with the primary tumor or metachronously, following treatment of localized disease. The objective of this study was to identify key prognostic factors influencing survival in synchronous metastases (SM) and metachronous metastases (MM), focusing on metastatic duration, tumor volume response, and gamma knife radiosurgery. MethodsA retrospective cohort study was conducted involving 100 patients with brain metastases (48 synchronous, 52 metachronous). Age, gender, primary tumor, gamma knife status, metastasis location, peritumoral index group, volume reduction, metastatic duration, metastasis characteristics, and intensity pattern based on MRI. A Cox proportional hazards regression was used to analyze the data. Based on the Cox regression coefficients, a prognostic index was constructed. ResultsCalculated HR comprised MM (HR=0.49;95% CI :0.24–0.97], gamma knife treatment (HR = 0.15;95% CI: 0.07–0.29], and volume response (HR=0.40;95% CI: 0.16–0.99), all indicating a significantly reduced mortality risk. A prognostic index was calculated for all patients; those with scores ≤–1.513 were classified as low risk. Kaplan-Meier analysis showed that the low-risk group had a significantly longer mean survival period (75.52 months) compared to the high-risk group (31.43 months) (p<0.001). ConclusionMetachronous presentation, gamma knife therapy, and greater tumor volume reduction independently predict better survival. The developed prognostic index provides a clinically useful tool for personalized risk assessment and treatment planning in patients with brain metastases.